Outcome of reconstruction of cutaneous limb defects in dogs using hygroscopic "self‐inflating" tissue expanders. (2nd November 2017) - De Lorenzi, M.; Swan, M. C.; Easter, C.; Chanoit, G. P. A.
Abstract : Objectives: To describe the placement of self‐inflating tissue expanders and clinical outcomes in 12 consecutive cases of reconstruction of distal cutaneous limb defects in dogs. Materials and Methods: Cases of distal cutaneous limb defect were divided into three groups based on the location of the placement of the self‐inflating tissue expanders: Group A (n=4): on, or proximal to, the elbow and stifle; Group B (n=4): distal to the elbow or stifle and proximal to the carpus or tarsus; and Group C (n=4): distal to the carpus or tarsus. Owner satisfaction and clinical outcome were documented. Results: Thirteen cases were originally included, but one was excluded because of incomplete follow‐up. In one case, the self‐inflating tissue expanders were removed before expansion started. A mean of five expanders were implanted per dog (range 2 to 9). Devices were removed after a mean of 24 days (range 13 to 42 days). Primary closure was achieved in eight of 11 cases, including all cases from Group A and 75% and 33% of cases from Groups B and C, respectively. All incompletely reconstructed defects or areas of wound dehiscence healed by second intention. Eight of 12 owners were satisfied. Clinical Significance: Self‐inflating tissue expanders can be used as an alternative for the reconstruction of limb defects in dogs in which direct primary closure would otherwise not be achievable. Defects below the carpus and tarsus are more challenging to treat with this method.